Pengaruh Gaya Belajar Terhadap Prestasi Peserta Didik - Rahmalika Putri; Marsofiyati Marsofiyati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to determine the influence of learning style on the learning outcomes of students. This research was conducted using a descriptive qualitative approach, describing or describing the influence of learning styles on student learning. The data collection technique used is the study of literature. The results of the research show that the learning style of students has three types of learning styles, each according to their comfort. How to find out the learning style that students have can be done by observation, survey, or learning style test. The strategy carried out to facilitate the learning process according to the learning style of students is to use visual material, encourage students to read the material in a loud voice, and invite children to learn while exploring the environment. Learning style is the key to improving academic achievement. Each student has a different learning style, so understanding the learning styles of different students will provide appropriate services for what and how should be provided and completed for learning that goes well.